On the (p,q)th Relative Order Oriented Growth Properties of Entire Functions - Luis Manuel Sánchez Ruiz; Sanjib Kumar Datta; Tanmay Biswas; Golok Kumar Mondal (Abstract and Applied Analysis)
The relative order of growth gives a quantitative assessment of how different functions scale each other and to what extent they are self-similar in growth. In this paper for any two positive integers p and q, we wish to introduce an alternative definition of relative (p,q)th order which improves the earlier definition of relative (p,q)th order as introduced by Lahiri and Banerjee (2005). Also in this paper we discuss some growth rates of entire functions on the basis of the improved definition of relative (p,q)th order with respect to another entire function and extend some earlier concepts as given by Lahiri and Banerjee (2005), providing some examples of entire functions whose growth rate can accordingly be studied.